Excitation energy transport and trapping in concentrated solid solutions of flavomononucleotide - Bojarski, P.; Kułak, L.; Grajek, H.; Żurkowska, G.; Kamińska, A.; Kukliński, B.; Bojarski, C. (Biochimica et biophysica acta, 2003)
Excitation energy transport and trapping is studied for monomer–fluorescent dimer system of flavomononucleotide (FMN) in polyvinyl alcohol films (PVA). It is shown that the theory neglecting reverse energy transfer (RET) from dimers to monomers does not allow for the explanation of concentration quenching and concentration depolarization results presented herein. Much better agreement has been obtained using generalized energy transport theory in which fluorescent dimers are treated as imperfect traps for excitation energy. Such parameters like the dimer quantum yield and its emission anisotropy are estimated.